Mediating Role of Resilience in the Relationship Between English Learners’ Motivation and Well-Being - Wang, Fei; Liu, Yanghong (Frontiers in Psychology, 2022)
Teaching seeks to enhance learners’ well-being as well as their educational motivation since both constructs cause advancement in the process of learning and they increase the level of success in the educational cycle. Well-being is a critical requirement inside the academic environment that is considered as the main dimension of individuals’ tendency in the topic of Positive Psychology (PP) research, which is crucial for learning. Besides, as a significant idea in language domain and in order to consider the relation between well-being and motivation, the other concept is arisen in PP, namely resilience that seems to be effective for learners as it deals with the capability to effectively manage difficulties in the past and present time in the learning process. As a result, this study considers the relationship between well-being and motivation; however, it also inspects the mediating role of resilience in this regard. Consequently, this review of literature holds suggestions for researchers, philosophers, and experts searching for better exploration and attention to the functions of resilience as a mediator in the relationship between learners’ motivation and well-being.